Geometric design method of lightweight line gear mechanism - Chen, Yangzhi (Strojniški vestnik, 2025)
Based on the space curve meshing theory, a lightweight line gear mechanism (LLGM) was proposed in this paper. The LLGM can achieve the objective of lightweight design by reducing the radial dimension of the gear, which has an improvement in terms of size reduction. The outstanding advantage of the LLGM is its ability to achieve a high transmission ratio. Three aspects were proposed to design the LLGM: first, the primary design method was obtained; second, an approach to simply and effectively establish the analytical model of the LLGM was presented, which showed that the lightweight characteristic of the LLGM is mainly reflected in the radial dimension; third, the discriminant condition of the LLGM was built. The simplicity and effectiveness of the LLGM were demonstrated by a design example, while gear contact simulation and kinematics experiments were carried out to verify the theoretical basis. The lightweight design method proposed in this paper belonged to structural lightweight design, which can effectively solve the lightweight design issue in gear transmissions characterized by light loads and high transmission ratios.
Keywords: gear design; high transmission ratio; kinematics experiments; kinematični poskusi; lahka zasnova; lightweight design; ozobljenje prostorske krivulje; space curve meshing; visoko prenosno razmerje; zasnova zobnikov